2008
DOI: 10.1007/s11095-008-9752-7
|View full text |Cite
|
Sign up to set email alerts
|

Major SNP (Q141K) Variant of Human ABC Transporter ABCG2 Undergoes Lysosomal and Proteasomal Degradations

Abstract: Purpose-Single nucleotide polymorphisms (SNPs) of the ATP-binding cassette (ABC) transporter ABCG2 gene have been suggested to be a significant factor in patients' responses to medication and/or the risk of diseases. We aimed to evaluate the impact of the major non-synonymous SNP Q141K on lysosomal and proteasomal degradations. Methods-ABCG2WT and the Q141K variant were expressed in Flp-In-293 cells by using the Flp recombinase system. Their expression levels and cellular localization was measured by immunoblo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
112
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 49 publications
7
112
1
1
Order By: Relevance
“…To investigate the opposing observations and to explore the possibility that both a loss of function and a expression defect could be caused by the Q141K mutation, we expressed our ABCG2 constructs in mammalian cell expression systems. We found, much like previous reports (12,13,15,18), that, in multiple mammalian cell lines, transient expression of the Q141K mutation resulted in significantly less total protein (Fig. S1 A and B and Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…To investigate the opposing observations and to explore the possibility that both a loss of function and a expression defect could be caused by the Q141K mutation, we expressed our ABCG2 constructs in mammalian cell expression systems. We found, much like previous reports (12,13,15,18), that, in multiple mammalian cell lines, transient expression of the Q141K mutation resulted in significantly less total protein (Fig. S1 A and B and Fig.…”
Section: Resultssupporting
confidence: 90%
“…However, in our heterologous Xenopus expression system we did not observe a reduction in protein expression levels in the mutant protein (Fig. 1A), unlike what had been reported previously (12,13,15,18). To investigate the opposing observations and to explore the possibility that both a loss of function and a expression defect could be caused by the Q141K mutation, we expressed our ABCG2 constructs in mammalian cell expression systems.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Indeed, N-linked glycans are thought to be crucial regulators of the stability of ABCG2 in the endoplasmic reticulum 8,9 . In fact, N-glycosylated wildtype ABCG2 is degraded in lysosomes, whereas misfolded mutant proteins have been shown to undergo ubiquitin-mediated degradation in the proteasome 10,11 . We have recently observed that increased levels of glycosylation-defective ABCC1 and ABCC4 are associated with resistance to platinum compounds in ovarian carcinoma cell lines 12 .…”
mentioning
confidence: 99%
“…Several studies consistently revealed that Q141K had a lower protein expression level than wild-type BCRP in both transfected cells and human tissues. A recent study has revealed that Q141K undergoes increased lysosomal and proteasomal degradations than wild-type BCRP, possibly explaining the lower level of protein expression of the variant [31]. The R482T and R482G variants of BCRP detected from MCF7/ AdVp3000 and S1-M1-80 cells belong to non-natural mutants.…”
Section: Breast Cancer Resistance Protein (Bcrp)mentioning
confidence: 99%